Government policies on the high composition between reality and hope - Theoretical study - Makhlouf, Samir; Bounif, Hanane (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2024)
This study aims to analyze government policies concerning universities in Algeria, focusing on recent strategies such as digital transformation, the introduction of new academic programs like seawater desalination and green hydrogen, and the emphasis on medical sciences training. Additionally, it explores amendments to training programs, including the integration of English language instruction across disciplines and the expansion of university facilities. These initiatives aim to enhance the academic reputation and global visibility of Algerian universities, particularly amidst a significant surge in scientific advancements and research worldwide. The study found that academic mobility as a new strategy in the university contributes to the valorisation of the Algerian student's path and his integration with the cultures and traditions that abound in the Algerian university, the digital transformation of the university contributes to its effectiveness and adaptation to global requirements, and enables the elimination of negative manifestations, and the strategy of opening university facilities, especially in the night period, such as libraries, business incubators and research laboratories, contributes effectively to increasing scientific achievement. The inclusion of the English language in scientific research also contributes to increasing the acquisition of new skills and access to scientific research and studies, it is a strategy that emphasises the government's endeavour to ensure the quality and sustainability of the university's presence in international forums. The strategy of opening new configurations contributes to strengthening the country's economy, linking the university to its social and economic surroundings and making it an active pole in economic and social development.